Very Early Involvement of Innate Immunity in Peripheral Nerve Degeneration in SOD1-G93A Mice - Angelini, Daniela Francesca; De Angelis, Federica; Vacca, Valentina; Piras, Eleonora; Parisi, Chiara; Nutini, Michele; Spalloni, Alida; Pagano, Francesca; Longone, Patrizia; Battistini, Luca; Pavone, Flaminia; Marinelli, Sara (Frontiers in Immunology, 2020)
RRecent preclinical and clinical evidence suggest that immune system has a role in the progression and prognosis of Amyotrophic Lateral Sclerosis (ALS), but the identification of a clear mechanism and immune players remains to be elucidated. Here, we have investigated, in 30 and 60 days (presymptomatic) and 120 days (symptomatic) old SOD1-G93A mice, systemic, peripheral and central innate and adaptive immune and inflammatory response, correlating it with the progression of the neurodegeneration in neuromuscular junction, sciatic nerves, and spinal cord. Surprisingly, we found a very initial (45 - 60 days) presence of IgG in sciatic nerves together with a gradual enhancement of A20/TNFAIP3 (protein controlling NF-κB signalling) and a concomitantly significant increase and activation of circulating mast cells (MCs) as well as MCs and macrophages in sciatic nerve and an enhancement of IL-6 and IL-10. This immunological frame coincided with a myelin aggregation. The 30-60 days old SOD1-G93A mice didn’t show real elements of neuroinflammation and neurodegeneration. In120 days old mice macrophages and monocytes are widely diffused in sciatic nerves, peripheral neurodegeneration reaches the tip, high circulating levels of TNF and IL-2 were found and spinal cord exhibits clear signs of neural damage and infiltrating immune cells. Our results underpin a clear immunological disorder at the origin of ALS axonopathy, in which MCs are involved in the initiation and sustaining of inflammatory events. These data cannot be considered a mere epiphenomenon of motor neuron degeneration and reveal new potential selective immune targets in ALS therapy.